Evaluation of changes in the cognitive function of adult cynomolgus monkeys under stress induced by audio-visual stimulation by applying modified finger maze test - Huang, Ying; Wang, Hong; Yang, Chen; Luo, Yuchong; Ding, Yongyan; Jin, Hongjun; Wen, Shenglin (Frontiers in Neuroscience, 2022)
Stress in life is ubiquitous and unavoidable. Prolonged exposure to severe stress can lead to physical intolerance and impair cognitive function. Non-human primates are considered to be the best animal model for studying cognitive function, especially memory and attention. The finger maze test, with the advantages of short training time and lower cost, is recommended to evaluate learning and memory in non-human primates. In this study, we modified the finger maze test method to evaluate cognitive function of single housed cynomolgus monkeys. The flexibility and attention of cynomolgus monkeys were assessed by performing the complex task test and the stranger intrusion interference test respectively, which increased the difficulty of obtaining rewards, and the ability of long-term memory was also evaluated by the memory test. Next, the changes in cognitive function of the cynomolgus monkeys were tested by using the finger maze test after audio-visual stimulation and changes in cortisol levels during stimulation were analyzed. We found that after completing the learning test, there was no significant decrease in their success rate when monkeys processed multitasks at the same time. In the stranger intrusion interference test, all subjects were distracted, but the accuracy did not decrease. The monkeys completed the memory tests at the first and second month after the learning tests, with a high success rate. However, the success rate decreased significantly at the end of fourth months. In the process of audio-visual stimulation, the plasma cortisol level significantly increased at the first two months and maintained at a high level after that. One month after audio-visual stimulation, the accuracy of the finger maze test was significantly reduced, and the total time of distraction was significantly prolonged. In conclusion, chronic audio-visual stimulation can increase blood cortisol level and impair cognitive function. The modified finger maze test can evaluate many aspects of cognitive function and assess the changes in cognitive function of the monkeys under stress.